FAULTING OF THE LITHOSPHERE IN THE CENTRAL ASIA AND ACCOMPANYING PROCESSES: TECTONOPHYSICAL APPROACH - K. Zh. Seminsky (Геодинамика и тектонофизика)
The article describes the history, the staff, researches and scientific activities of the Laboratory of Tectonophysics of the Institute of the Earth’s Crust, which are focused on problems of faulting in the lithosphere. The Laboratory was established 35 years ago. The article reviews the major results of scientific research projects implemented from 2009 to 2013. The main objects of the complete cycle of tectonophysical studies were the zone-block structure of the lithosphere in the Central Asia, fault tectonics, stress fields, mechanisms of formation and seismicity of the Baikal rift zone, emanation activity of crustal faults, regimes of displacements at fault segments etc. It is shown that the team of the Laboratory views its scientific prospects in development of comprehensive models of inter-block zone of destruction, taking into account regular fault patterns and regularities of accompanying processes (such as seismic, emanation and other types of activity) which are predetermined by such fault patterns.